(untitled) (Tribhuvan University Journal of Microbiology, 2024)
Objectives: To characterize the etiology of infectious vaginitis among reproductive-aged women visiting a tertiary care hospital in Nepal. Methods: The vaginal samples were collected from woman with abnormal vaginal discharge. Nugent’s score system and Amsel’s criteria were used in diagnosing bacterial vaginosis (BV), wet mount preparation was done to diagnose trichomonal vaginitis (TV), and Aerobic vaginitis (AV), and vulvovaginal candidiasis (VVC) were diagnosed by culture method. Clinical and Laboratory Standards Institute (CLSI) guidelines were used to assess the antimicrobial susceptibility profile of aerobic bacteria and Candida isolates. Results: Out of 141 reproductive-aged women included, 60.3% presented with thin and scanty vaginal discharge, 52.5% had clear to white discharge, and 39.0% had vulvovaginal itching. The overall rate of any type of infectious vaginitis was 44.0% with the predominance of BV (19.8%) followed by AV (12.8%), VVC (11.3%), and TV (7.1%). Infectious vaginitis was frequent among women between the age of 25 and 34 years. BV was significantly associated with malodorous discharge (p = 0.002) and VVC was significantly higher in women with vulvovaginal itching (p = 0.009). The most common aerobic bacteria that caused AV was Escherichia coli, while Candida albicans represented the most common cause of VVC. Conclusion: Incorporating simple laboratory test in management of vaginal discharge cases helps identify correct etiology minimizing the disease burden with appropriate use of antibiotics.